Antibiofilm Activity of Small-Molecule ZY-214-4 Against Staphylococcus aureus - Yu, Jingyi; Rao, Lulin; Zhan, Lingling; Zhou, Yan; Guo, Yinjuan; Wu, Xiaocui; Song, Zengqiang; Yu, Fangyou (Frontiers in Microbiology, 2021)
Staphylococcus aureus is the most important pathogenic bacteria in humans. As the resistance of S. aureus to existing antibiotics is increasing, there is an urgent need for new anti-infective drugs. S. aureus biofilms cause persistent infections and resist complete eradication with antibiotic therapy. The present study investigated the inhibitory effect of the novel small-molecule ZY-214-4 (C19H11BrNO4) on S. aureus biofilm formation. At a subinhibitory concentration (4 μg/ml), ZY-214-4 had no effect on the growth of S. aureus strains and also showed no cytotoxicity in human normal bronchial epithelial cells (Bease-2B). The results of a semi-quantitative biofilm test showed that ZY-214-4 prevented S. aureus biofilm formation, which was confirmed by scanning electron microscopy and confocal laser scanning microscopy. ZY-214-4 significantly suppressed the production of polysaccharide intercellular adhesion and prevented cell aggregation, and also inhibited the mRNA expression of icaA and other biofilm-related genes (eno, clfA/B, fnbB, fib, ebpS, psmα, and psmβ) in clinical S. aureus isolates. Thus, at a subinhibitory concentration, ZY-214-4 inhibits biofilm formation by preventing cell aggregation, highlighting its clinical potential for preventing or treating S. aureus infections.